The Increase of Students Science Cognitive using Snake Ladder Media - Amin, Mohammad Latiful; Sulistyorini, Sri; Sugianto, Sugianto (Journal of Primary Education)
The purpose of the study was to determine the increase in science cognitive of students using snake ladder media. This study is quantitative research design by applying Pre-test – Post-test Control Group Design. The initial stage in the experimental class treated using snake ladder media, whereas, the control class treated by simple experiment. The subjects of the study were 65 Elementary school students who were participated in the implementation of this study with the population of Gugus Pattimura in Mejobo, Kudus. The data collection technique was using the learning outcomes test techniques with multiple choice type questions. The data analysis technique applied was quantitative descriptive analysis techniques. The results of this study indicated that there is an increase in the acquisition of science cognitive of students using snakes ladders media. The average pre-test scores were 60, meanwhile, the average post-test scores 72. The gain score of the pre-test and post-test data is 0.3 in moderate criteria. Therefore, it can be concluded that the use of snakes ladders media can income students science cognitive.